Diurnal dynamics of the СО2 concentration in water of the coastal zone of lake Baikal in the ice period (testing of the DIEL - CO2 method for assessment of lake metabolic rate); Proceedings of SPIE; Vol. 10466 : 23rd International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics - Panchenko M. V. Mikhail Vasiljevich; Domysheva V. M. Valentina Mikhaylovna; Pestunov D. A. Dmitry Aleksandrovich; Sakirko M. V. Mariya Vladimirovna; Ivanov V. G. Vyacheslav Gennadjevich; Shamrin A. M. Artyom Mikhaylovich (2017, 2017)
Title screen